Genetically-Engineered Pig-to-Baboon Liver Xenotransplantation: Histopathology of Xenografts and Native Organs (2012)
Orthotopic liver transplantation was carried out in baboons using wild-type (WT, n = 1) or genetically-engineered pigs (a1,3- galactosyltransferase gene-knockout, GTKO), n = 1; GTKO pigs transgenic for human CD46, n = 7) and a clinically-acceptable immunosuppressive regimen. Biopsies were obtained from the WT pig liver pre-Tx and at 30 min, 1, 2, 3, 4 and 5 h posttransplantation. Biopsies of genetically-engineered livers were obtained pre-Tx, 2 h after reperfusion and at necropsy (4–7 days after transplantation). Tissues were examined by light, confocal, and electron microscopy. All major native organs were also examined. The WT pig liver underwent hyperacute rejection. After genetically-engineered pig liver transplantation, hyperacute rejection did not occur. Survival was limited to 4–7 days due to repeated spontaneous bleeding in the liver and native organs (as a result of profound thrombocytopenia) which necessitated euthanasia. At 2 h, graft histology was largely normal. At necropsy, genetically-engineered pig livers showed hemorrhagic necrosis, platelet aggregation, platelet-fibrin thrombi, monocyte/macrophage margination mainly in liver sinusoids, and vascular endothelial cell hypertrophy, confirmed by confocal and electron microscopy. Immunohistochemistry showed minimal deposition of IgM, and almost absence of IgG, C3, C4d, C5b-9, and of a cellular infiltrate, suggesting that neither antibody- nor cell-mediated rejection played a major role.